2022
DOI: 10.1002/vms3.814
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial and toxicological aspects of zinc oxide nanoparticles in animals

Abstract: Nanotechnology is a far‐reaching technology with tremendous applications in various aspects, including general medicine, veterinary medicine, agriculture, aquaculture, and food production. Nanomaterials have exceptional physicochemical characteristics, including increased intestinal absorption, biodistribution, bioavailability, and improved antimicrobial and catalytic properties. Although nanotechnology is gaining ground in animal management, husbandry, and production, its wide use is still hampered by occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Moreover, Rajkumar et al demonstrated that administration of ZnO-NPs to Cyprinus carpio resulted in degeneration of liver tissues, vacuolization, cell infiltration, and nuclear alteration [ 13 ]. Furthermore, ZnO-NPs were reported to damage the hepatic tissue as evidenced by elevated liver enzyme markers in the serum of Oreochromis niloticus and C. carpio [ 20 , 21 , 24 ] and decreased serum albumin and total protein [ 21 ]. The induced structural changes in the liver of ZnO-NPs-exposed fishes could be attributed to hepatic oxidative damage with an increased rate of lipid peroxidation and suppression of antioxidant enzymes [ 11 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Rajkumar et al demonstrated that administration of ZnO-NPs to Cyprinus carpio resulted in degeneration of liver tissues, vacuolization, cell infiltration, and nuclear alteration [ 13 ]. Furthermore, ZnO-NPs were reported to damage the hepatic tissue as evidenced by elevated liver enzyme markers in the serum of Oreochromis niloticus and C. carpio [ 20 , 21 , 24 ] and decreased serum albumin and total protein [ 21 ]. The induced structural changes in the liver of ZnO-NPs-exposed fishes could be attributed to hepatic oxidative damage with an increased rate of lipid peroxidation and suppression of antioxidant enzymes [ 11 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the liver is a key metabolic organ responsible for many vital functions including energy metabolism and detoxification of various environmental pollutants [ 17 , 18 , 19 ]. The hepatotoxicity associated with ZnO-NPs exposure was previously reported in the Oreochromis niloticus [ 20 , 21 , 22 , 23 ] and Cyprinus carpio [ 24 ] indicated by increasing the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) and the reduction in serum activity of protein and albumin all were observed along with elevation of total triglycerides and cholesterol in serum. Related to liver function, carbohydrates and lipids are the main sources of energy production in living organisms and contribute to many vital processes including development and reproduction [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NP) are being produced and used at an increasing rate, it is intermediate phase between bulk and molecules particles, and they are more toxic to human and environment health than bulk materials due to their increased surface reactivity and small size, which enable them to enter and concentrate inside of cells (30,31). Zinc oxide (ZnO) nanoparticles is one of the most nanomaterials, used in many in application and dustries such as sunscreens, cosmetics, ceramics, UV filters and paints photocatalysis, so it impacts the aquatic environment both directly and indirectly, and cause eco-toxicity and affected public health (32,33).…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 85 Of note, the accumulation of Zn in kidney tissues and the development of toxicity must be avoided, which requires the regulation of the dose of the drug to the organism within a strict safety threshold. 86 …”
Section: Research Progress In Nanoplatforms In the Treatment Of Dnmentioning
confidence: 99%